Influence of Malnutrition According to the GLIM Criteria on the Clinical Outcomes of Hospitalized Patients With Cancer - Liu, Chengyu; Lu, Zhenhua; Li, Zijian; Xu, Jingyong; Cui, Hongyuan; Zhu, Mingwei (Frontiers in Nutrition, 2021)
Background: Malnutrition is prevalent among cancer patients. The Global Leadership Initiative on Malnutrition (GLIM) released new universal criteria for diagnosing malnutrition in 2019. The objectives of this study were to assess the prevalence of malnutrition in cancer patients using the GLIM criteria, explore the correlation between the GLIM criteria and clinical outcomes, and compare the GLIM criteria with subjective global assessment (SGA). Methods: This retrospective analysis was conducted on 2388 cancer patients enrolled in a multicenter study. Nutritional risk was screened using the Nutritional Risk Screening-2002, and the nutritional status was assessed using SGA and GLIM criteria. Chi-square analysis and Wilcoxon rank sum test, stratified by age 65 years, were used to evaluate the effect of GLIM-defined malnutrition on clinical outcomes. Logistic regression analysis was used to analyze nutritional status and complications, and the interrater reliability was measured using a kappa test. Results: The prevalence of malnutrition defined by the GLIM criteria was 38.9% (929/2388). GLIM-defined malnutrition was significantly associated with in-hospital mortality (P = 0.001) and length of hospital stays (P = 0.001). Multivariate logistic regression analysis showed GLIM-defined malnutrition significantly increased complications (odds ratio 1.716, 95% confidence interval 1.227–2.400, P = 0.002). The GLIM criteria had a “moderate agreement” (kappa = 0.426) compared with the SGA. Conclusions: The prevalence of malnutrition in hospitalized cancer patients is high, and malnourishment in cancer patients is associated with poorer clinical outcomes. The use of the GLIM criteria in assessing the nutritional status of cancer inpatients is recommended and can be used as the basis for nutritional interventions.